2023
DOI: 10.3390/healthcare11050675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin Supplementation on Sleep Quality in Breast Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: Evidence on the effectiveness of melatonin in breast cancer patients suffering from sleep disturbances is contradictory, and there have been no meta-analyses on its use in humans with breast cancer. This study investigated the melatonin supplementation effectiveness in alleviating sleep disturbances in breast cancer patients. We searched Embase, PubMed, MEDLINE, CINAHL, Cochrane Library, Google Scholar, and Clinical trial.org databases for relevant reports by following PRISMA guidelines and collected clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Similarly, Chen and co-workers observed that oral melatonin administration in BC survivors improved sleep efficiency [49]. Deficiencies in the production or synthesis of endogenous melatonin have been found to be associated with the onset of many disorders like BC [50,51]. Sleep disorders are frequent in the general population, and cancer has been reported to activate sleep disorders itself [52,53].…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, Chen and co-workers observed that oral melatonin administration in BC survivors improved sleep efficiency [49]. Deficiencies in the production or synthesis of endogenous melatonin have been found to be associated with the onset of many disorders like BC [50,51]. Sleep disorders are frequent in the general population, and cancer has been reported to activate sleep disorders itself [52,53].…”
Section: Discussionmentioning
confidence: 95%
“…Yapılan bir meta-analiz çalışması, melatonin alımının meme kanseri hastalarında uyku kalitesini özellikle adjuvan tedavi alan hastalarda iyileştirdiğini göstermiştir. Ancak yan etkileriyle ilgili daha fazla çalışmaya ihtiyaç vardır (6,7). Ek olarak, orexin reseptör antagonistleri rexin reseptörlerine bağlanarak oreksin sinyallerini bloke ederler ve böylece uykuya dalmayı kolaylaştırırlar (6).…”
unclassified